A genetically enhanced sterile insect technique against the fruit fly, Bactrocera dorsalis (Hendel) by feeding adult double-stranded RNAs - Muhammad Waqar Ali (Nature Portfolio, 2017)
Abstract RNAi based sterile insect technique (SIT) is an authentic insect management approach but requires proper target genes. During this study, spermless males were developed by interfering with germ cell differentiation and azoospermia related genes. Data demonstrates significant reductions in the target genes expressions (boul, zpg, dsx M , fzo and gas8) after oral dsRNAs administration. Knock down of target genes significantly affected the reproductive ability of males and reduced egg-hatching as compared to the control group. Furthermore, different combinations of selected gene dsRNAs (boul + zpg, boul + dsx M and zpg + dsx M ) were made, which resulted up to 85.40% of male sterility. The most effective combination was selected to prepare different concentrations of dsRNA, 250, 500, 750 and 1000 ng/μl, that caused 18.97%, 38.68%, 58.02% and 85.40% male sterility, respectively. Subsequently, 1000 ng/μl of the same combination of ds-RNAs was used against differently aged adult flies (1, 5, 7, 10 days) which lead to 85.40%, 31.42%, 21.76% and 9.90% male sterility, respectively. SIT developed in this study showed that, boul + zpg combination of dsRNA feeding for 6 hours significantly reduced the number of spermatozoa and viability of sperm in 1-day-old B. dorsalis flies. In short, this study provides an effective SIT technique for long-term B. dorsalis management.